Tirofiban as Treatment for Acute Retinal Artery Occlusion following Internal Carotid Artery Flow Diverter Implantation. Issue 4 (July 2016) - Pierro, Luisa; La Spina, Carlo; Corvi, Federico; Cicinelli, Maria V.; Scomazzoni, Francesco; Cappelletti, Alberto; Bandello, Francesco
Purpose: To report a favorable outcome of branch retinal artery occlusion (BRAO) treated by means of early administration of tirofiban, a glycoprotein IIb-IIIa platelet receptor inhibitor. Methods: Case report. Results: A 65-year-old woman developed dramatic visual impairment in her left eye secondary to BRAO after left internal carotid artery endovascular reconstruction with flow diverter stent implant; visual acuity was hand motion. A dose of intravenous tirofiban was injected 10 minutes after symptoms onset. Fourteen hours after drug infusion, retinal fluorescein angiography revealed a well-perfused macula with a partial reperfusion of the inferior temporal branch of the central retinal artery; visual acuity was 20/20 in both eyes. Conclusions: This case supports the effectiveness of tirofiban in secondary BRAO in neurosurgery and may open its usage to further research.